PROFILACTIСS OF CORRUPTION IN THE FIELD OF HIGHER EDUCATION - M. A. Gribkov (Модернизация, инновация, развитие)
Corruption turnover in Russia makes at present about 50% of Gross Internal Product. Higher education is one of most corruption prone activity fields. Spheres of higher education most subject to corruption are entry to higher schools and passing exams/tests. In the context of anticorruption measures, monitoring is of special importance. Anticorruption practice in Russian Plekhanov University of Economics is discussed.